Perilaku Konsumen dalam Perspektif Ekonomi Islam: Teori dan Praktek - Hasan Sultoni (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Islam sees economic activity is one way to accumulate and increase the reward to the falah (happiness of the world and the Hereafter). Motif consume in Islam is basically mashlahah, needs and obligations. Satisfaction of a Muslim is not based market more or less items that can be consumed, but based on how religious values ​​obtained from what it does. In the teachings of the Islamic religion for the purpose of consumption is the biggest maslahah, so that he can achieve victory in duina and hereafter. Satisfaction in Islam include consumer satisfaction and creative satisfaction, consumer satisfaction will produce the ready creation of satisfaction, because the consumption made by a Muslim would give his physical strength, so he can be more creative. To measure the satisfaction of a Muslim we can use the concept of conventional utilities. As for rational human behavior in the conduct of consumption when he can maximize the values ​​of conformity in accordance with the norms of Islam.